Preparation method of stannic oxide-based nano material, VOC (volatile organic compound) gas sensor and preparation method

Through a simplified preparation method, tin dioxide-based nanomaterials with high gas-sensitive properties are prepared by using hydrothermal reaction and sintering treatment steps, solving the problems of cumbersome preparation and low response sensitivity of existing SnO2 materials.

CN119551712APending Publication Date: 2025-03-04SHENZHEN HUITOU INTELLIGENT CONTROL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411682421.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The preparation process of existing SnO2 gas-sensitive materials is complicated and has low sensitivity to VOCs gases.

Method used

Using a preparation method including steps of mixing, hydrothermal reaction and sintering treatment, a tin dioxide-based nanomaterial is prepared by mixing a tin source and a dispersant in a solvent, adjusting the pH value to carry out hydrothermal reaction, forming a microsphere precursor, and tin dioxide-based nanomaterial is prepared by sintering treatment.

Benefits of technology

This method simplifies the preparation process, improves the gas-sensitive performance of tin dioxide-based nanomaterials, and enhances the response sensitivity and structural stability to VOCs gas.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119551712A_ABST
    Figure CN119551712A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of gas detection, in particular to a preparation method of a stannic oxide-based nano material, a VOC (volatile organic compound) gas sensor and a preparation method. The preparation method of the stannic oxide-based nano material provided by the invention comprises the following steps: mixing a tin source and a dispersing agent in a first solvent to prepare a mixed solution; adjusting the pH value of the mixed solution to 3.8-13.5, carrying out a hydrothermal reaction, carrying out solid-liquid separation, and collecting a solid-phase substance to prepare a microsphere precursor; and carrying out sintering treatment on the microsphere precursor to prepare the stannic oxide-based nano material. The preparation method provided by the invention is simple in process, and the gas-sensitive property of the stannic oxide-based nano material can be effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of gas detection technology, and in particular to a method for preparing a tin dioxide-based nanomaterial, a VOC gas sensor and a preparation method thereof. Background Art

[0002] Volatile organic compounds (VOCs) refer to a class of organic substances that have a melting point higher than room temperature and a boiling point between 50°C and 260°C, and often exist in the air in the form of vapor at room temperature. VOCs are irritating, toxic, and carcinogenic, and long-term exposure to VOCs can damage human health.

[0003] There are many detection methods such as mass spectrometry, fluorescence spectroscopy, ion chromatography, photoacoustic spectroscopy, etc., which can be used to detect VOCs. However, these detection methods basically require sampling, sample pretreatment and detection, which are complicated and time-consuming, and the detection equipment is expensive. Gas sensors have the advantages of low cost, small device size, and easy integration, and have attracted widespread attention.

[0004] When the gas-sensitive material layer in the gas sensor comes into contact with VOCs gas, physical or chemical changes will occur. These changes will cause the electrical signals of the sensor (such as resistance, current, etc.) to change. By measuring the changes in these electrical signals, the concentration of the gas can be inferred. At present, the gas-sensitive materials used are mainly metal oxide semiconductors (MOS) with low cost and good stability. Among them, SnO2, as an n-type wide-bandgap semiconductor, responds to most VOCs gases, but the current preparation process of SnO2 is cumbersome, and the prepared SnO2 still has the disadvantage of low sensitivity. Summary of the invention

[0005] Based on this, the present application provides a preparation method of tin dioxide-based nanomaterials, a VOC gas sensor and a preparation method. The preparation method provided in the present application has a simple process and can effectively improve the gas sensing performance of tin dioxide-based nanomaterials.

[0006] In a first aspect of the present application, a method for preparing a tin dioxide-based nanomaterial is provided, comprising the following steps:

[0007] Mixing a tin source and a dispersant in a first solvent to prepare a mixed solution;

[0008] The pH of the mixed solution is adjusted to 3.8-13.5, a hydrothermal reaction is performed, and after solid-liquid separation, a solid phase is collected to prepare a microsphere precursor;

[0009] The microsphere precursor is sintered to prepare the tin dioxide-based nanomaterial.

[0010] In one embodiment, the step of preparing the mixed solution has one or more of the following characteristics:

[0011] (1) The tin source includes one or more of SnCl4·5H2O, Na2SnO3 and SnCl2;

[0012] (2) The first solvent includes an alcohol solvent and water in a volume ratio of 1: (0.5-5).

[0013] In one embodiment, the dispersant comprises a citrate; the citrate has one or more of the following characteristics:

[0014] (1) The mass ratio of the tin source to the citrate is (0.8-1.8):(1.2-2.6);

[0015] (2) The citrate includes one or more of sodium citrate, potassium citrate, ammonium citrate, zinc citrate and magnesium citrate.

[0016] In one embodiment, the dispersant includes tetraaminopalladium nitrate;

[0017] The tin dioxide-based nanomaterial includes palladium element and tin dioxide, and the mass ratio of the palladium element to the tin dioxide is (0.003-0.05):1.

[0018] In one embodiment, after the step of sintering the microsphere precursor, the method further comprises:

[0019] The sintered body obtained by sintering treatment and the doped metal source are mixed in a second solvent, and after removing the solvent, heat treatment is performed to prepare the tin dioxide-based nanomaterial.

[0020] In one embodiment, the preparation method has one or more of the following characteristics:

[0021] (1) When the dispersant comprises citrate, the doping metal source comprises one or more of antimony trichloride and tetraaminopalladium nitrate;

[0022] (2) When the dispersant includes tetraaminopalladium nitrate, the doping metal source includes antimony trichloride;

[0023] (3) The process parameters of the heat treatment include: a treatment temperature of 400°C to 600°C and a treatment time of 1h to 4h.

[0024] In one embodiment, the step of preparing the microsphere precursor has one or more of the following characteristics:

[0025] (1) The reagent for adjusting the pH of the mixed solution to 3.8-13.5 is a pH adjuster, and the pH adjuster includes one or more of NaOH, KOH and ammonia water;

[0026] (2) The temperature of the hydrothermal reaction is 180°C to 200°C;

[0027] (3) The hydrothermal reaction time is 12h~24h.

[0028] In one embodiment, the sintering process has one or more of the following characteristics:

[0029] (1) The sintering temperature is 400°C to 600°C;

[0030] (2) The sintering time is 1h~4h.

[0031] In a second aspect of the present application, a VOC gas sensor is provided, comprising a MEMS chip and a gas-sensitive layer arranged on the surface of the MEMS chip, wherein the gas-sensitive layer comprises a tin dioxide-based nanomaterial prepared by the preparation method described in any embodiment of the first aspect of the present application.

[0032] The third aspect of the present application provides a method for preparing the VOC gas sensor according to the second aspect of the present application, comprising the following steps:

[0033] Mixing the tin dioxide-based nanomaterial prepared by the preparation method described in any one of the first aspects of the present application with a third solvent to prepare a gas-sensitive layer slurry;

[0034] The gas-sensitive layer slurry is coated on the surface of the MEMS sheet, and after film formation, a solvent removal treatment is performed to prepare the VOC gas sensor.

[0035] The beneficial effects of the preparation method of tin dioxide-based nanomaterials provided in the present application include at least:

[0036] In the preparation method provided by the present application, the tin source and the dispersant are first mixed in a first solvent, at which time the dispersant can form a stable complex with the tin ions and can help disperse the tin ions. After further adjusting the pH of the mixed solution, a hydrothermal treatment is performed, at which time the morphology and size of the precursor can be guaranteed to form a microsphere precursor with a high specific surface area and a uniform structure. The microsphere precursor is further sintered, which helps to reduce defects and vacancies to improve the crystallinity and structural stability of the material.

[0037] Therefore, the tin dioxide-based nanomaterial prepared by the preparation method provided in the present application has a higher specific surface area and fewer defects. Therefore, when it comes into contact with VOCs molecules, it can provide more surface active sites, thereby improving the gas-sensitive response; at the same time, the reduced defects and vacancies enhance the structural stability of the material, which is conducive to ensuring conductivity and gas-sensitive response speed.

[0038] Furthermore, the preparation method provided in the present application includes the steps of mixing, hydrothermal reaction and sintering treatment. The above steps are simple to operate, do not require complicated equipment and technology, and are easy to mass produce and apply. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 This is a SEM image of the tin dioxide-based nanomaterial prepared in Example 4 of the present application. DETAILED DESCRIPTION

[0040] The following is a further complete and clear description of the preparation method of the tin dioxide-based nanomaterial, the VOC gas sensor and the preparation method of the present application in conjunction with specific examples. The present application can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present application more thorough and comprehensive.

[0041] In a first aspect of the present application, a method for preparing a tin dioxide-based nanomaterial is provided, comprising the following steps:

[0042] S10, mixing the tin source and the dispersant in the first solvent to prepare a mixed solution.

[0043] S20, adjusting the pH of the mixed solution to 3.8-13.5, performing a hydrothermal reaction, and collecting the solid phase after solid-liquid separation to prepare a microsphere precursor.

[0044] S30, sintering the microsphere precursor to prepare the tin dioxide-based nanomaterial.

[0045] The present application has found that mixing the tin source and the dispersant in a solvent first is more helpful to ensure the dispersion of the tin ions. The tin source is the tin element provider for generating tin dioxide and is the basic substance for the reaction. The dispersant can react with the tin ions in the tin source to form a stable complex. This complexing reaction can control the concentration and reactivity of the tin ions in the solution, prevent the tin ions from precipitating prematurely or reacting unevenly, and provide a uniform reaction environment for the subsequent hydrothermal reaction.

[0046] The pH value of the mixed solution is further adjusted. At this time, the acidity and alkalinity of the mixed solution can be changed so that the pH value of the system reaches a condition suitable for the hydrothermal reaction; then a hydrothermal treatment is performed, which can effectively improve the reaction activity of the reactants, convert the tin ions into a precursor of tin dioxide, and ensure the morphology and size of the precursor to form a microsphere precursor with a high specific surface area and a uniform structure.

[0047] The microsphere precursor is then sintered to decompose and volatilize the organic components and impurities in the precursor, while converting the tin compounds into tin dioxide. At the same time, during the sintering process, the structure and composition of the microsphere precursor will change, gradually forming a crystalline structure of tin dioxide, thereby improving the crystallinity and structural stability of the material.

[0048] Therefore, the tin dioxide-based nanomaterial prepared by the preparation method provided in the present application has a higher specific surface area and fewer defects. Therefore, when it comes into contact with VOCs molecules, it can provide more surface active sites, thereby improving the gas-sensitive response; at the same time, the reduced defects and vacancies enhance the structural stability of the material, which is conducive to ensuring conductivity and gas-sensitive response speed.

[0049] Furthermore, the preparation method provided in the present application includes the steps of mixing, hydrothermal reaction and sintering treatment. The above steps are simple to operate, do not require complicated equipment and technology, and are easy to mass produce and apply.

[0050] In one example, in step S10, the tin source includes one or more of SnCl4·5H2O, Na2SnO3 and SnCl2.

[0051] Furthermore, the tin source includes SnCl4·5H2O.

[0052] SnCl4·5H2O will ionize in the solvent to produce Sn 4+ , Sn 4+ It has high chemical activity and can easily participate in chemical reactions during mixing with dispersants and subsequent hydrothermal reactions and sintering processes.

[0053] In one example, in step S10, the dispersant includes citrate.

[0054] The citrate ion in citrate has multiple 4+ The citrate ion can form a stable complex with the tin ion through the oxygen atom on its carboxyl group, and this complexation can effectively control the concentration and activity of the tin ion in the solution. In one example, the citrate salt includes one or more of sodium citrate, potassium citrate, ammonium citrate, zinc citrate and magnesium citrate.

[0055] In one example, in step S10, the first solvent includes an alcohol solvent and water in a volume ratio of 1: (0.5-5). For example, the volume ratio of the alcohol solvent to water is 1:0.5, 1:0.8, 1:1, 1:1.5, 1:2, 1:2.5, 1:3, 1:3.5, 1:4, 1:4.5 or 1:5, or any two of the above point values ​​are used as endpoint values. For example, the alcohol solvent includes but is not limited to methanol or ethanol.

[0056] In one example, in step S10, the mass ratio of the tin source to the citrate is (0.8-1.8):(1.2-2.6). For example, the mass ratio of the tin source to the citrate includes but is not limited to 0.8:1.2, 0.9:1.3, 1:1.4, 1.1:1.5, 1.2:1.6, 1.7:2.5, 1.75:2.6 or 1.8:2.6, or a range formed by any two of the above point values ​​as endpoint values.

[0057] In another example, in step S10, the dispersant includes tetraaminopalladium nitrate.

[0058] Furthermore, the dispersant comprises an aqueous solution of tetraminated palladium nitrate. Furthermore, in the aqueous solution of tetraminated palladium nitrate, the mass concentration of tetraminated palladium nitrate is 8% to 12%.

[0059] Further, when the tin source and the tetraamino palladium nitrate aqueous solution are mixed, the mass ratio of the tetraamino palladium nitrate included in the tin source and the tetraamino palladium nitrate aqueous solution is (0.8-1.5): (0.002-0.01). For example, the mass ratio of the tetraamino palladium nitrate included in the tin source and the tetraamino palladium nitrate aqueous solution includes but is not limited to 0.8:0.002, 0.9:0.004, 1:0.006, 1.1:0.006, 1.15:0.006, 1.17:0.006, 1.2:0.008, 1.3:0.009 or 1.5:0.01, or in the range formed by any two of the above ratios as endpoint values.

[0060] Furthermore, when the dispersant includes tetraamino palladium nitrate, the tin dioxide-based nanomaterial includes palladium element and tin dioxide, and the mass ratio of the palladium element to the tin dioxide is (0.003-0.05): 1. For example, the mass ratio of the palladium element to the tin dioxide includes but is not limited to 0.003: 1, 0.005: 1, 0.008: 1, 0.01: 1, 0.015: 1, 0.02: 1, 0.025: 1, 0.03: 1, 0.035: 1, 0.04: 1, 0.045: 1 or 0.05: 1, or within the range formed by any two of the above ratios as endpoint values.

[0061] The present application found that further doping tin dioxide with antimony or palladium can effectively increase the specific surface area of ​​the nanomaterial and construct a heterojunction, thereby improving the gas sensing performance. In addition, tetraaminopalladium nitrate can also effectively disperse the tin source, thereby reducing the difficulty of preparation.

[0062] In one example, after the step of sintering the microsphere precursor, the method further includes:

[0063] The sintered body obtained by sintering treatment and the doped metal source are mixed in a second solvent, and after removing the solvent, heat treatment is performed to prepare the tin dioxide-based nanomaterial.

[0064] In one example, when the dispersant includes citrate, the doping metal source includes one or more of antimony trichloride and tetraaminopalladium nitrate.

[0065] Further, when the dispersant includes citrate, the mass ratio of the sintered body to the antimony trichloride is 1:(0.001~0.01). For example, when the dispersant includes citrate, the mass ratio of the sintered body to the antimony trichloride includes but is not limited to 1:0.001, 1:0.0011, 1:0.0013, 1:0.0015, 1:0.0017, 1:0.0019, 1:0.002, 1:0.0022, 1:0.0022, 1:0.0025, 1:0.0027, 1:0.003, 1:0.005, 1:0.008 or 1:0.01, or any two of the above ratios are used as endpoint values. Further, the metal doping source is an antimony trichloride alcohol solution. In the antimony trichloride alcohol solution, the mass concentration of antimony trichloride is 0.8%~1.5%.

[0066] Further, when the dispersant includes citrate, the mass ratio of the sintered body to the tetraamino palladium nitrate is 1:(0.01~0.1). For example, when the dispersant includes citrate, the mass ratio of the sintered body to the tetraamino palladium nitrate includes but is not limited to 1:0.01, 1:0.011, 1:0.013, 1:0.015, 1:0.017, 1:0.019, 1:0.02, 1:0.022, 1:0.025, 1:0.027, 1:0.03, 1:0.04, 1:0.05, 1:0.06, 1:0.07, 1:0.08, 1:0.09 or 1:0.1, or any two of the above ratios are used as endpoint values. Further, the metal doping source is an aqueous solution of tetraamino palladium nitrate. In the tetraamine palladium nitrate aqueous solution, the mass concentration of the tetraamine palladium nitrate is 8% to 10%.

[0067] In one example, when the dispersant includes citrate, the doping metal source includes antimony trichloride, and the tin dioxide-based nanomaterial includes antimony element and tin dioxide. The mass ratio of the antimony element to the tin dioxide is (0.0003-0.06):1. For example, the mass ratio of the antimony element to the tin dioxide includes but is not limited to 0.0003:1, 0.0005:1, 0.0008:1, 0.001:1, 0.0015:1, 0.002:1, 0.0025:1, 0.003:1, 0.0035:1, 0.004:1, 0.0045:1, 0.005:1, 0.0055:1, 0.006:1, 0.008:1, 0.01:1, 0.02:1, 0.03:1, 0.04:1, 0.05:1 or 0.06:1, or in the range formed by any two of the above ratios as endpoint values.

[0068] In one example, when the dispersant includes citrate, the doping metal source includes tetraamino palladium nitrate, and the tin dioxide-based nanomaterial includes palladium element and tin dioxide. The mass ratio of the palladium element to the tin dioxide is (0.003~0.05):1. For example, the mass ratio of the palladium element to the tin dioxide includes but is not limited to 0.003:1, 0.005:1, 0.008:1, 0.01:1, 0.015:1, 0.02:1, 0.025:1, 0.03:1, 0.035:1, 0.04:1, 0.045:1 or 0.05:1, or any two of the above ratios as the range of endpoint values.

[0069] In another example, when the dispersant includes tetraaminopalladium nitrate, the doping metal source includes antimony trichloride.

[0070] Further, when the dispersant includes tetraamine palladium nitrate, the mass ratio of the sintered body to the antimony trichloride is 1:(0.001~0.01). For example, when the dispersant includes tetraamine palladium nitrate, the mass ratio of the sintered body to the antimony trichloride includes but is not limited to 1:0.001, 1:0.0011, 1:0.0013, 1:0.0015, 1:0.0017, 1:0.0019, 1:0.002, 1:0.0022, 1:0.0022, 1:0.0025, 1:0.0027, 1:0.003, 1:0.005, 1:0.008 or 1:0.01, or any two of the above ratios are used as endpoint values. Further, the metal doping source is an alcohol solution of antimony trichloride. In the antimony trichloride alcohol solution, the mass concentration of antimony trichloride is 0.8% to 1.5%.

[0071] In one example, when the dispersant includes tetraamino palladium nitrate, the doping metal source includes antimony trichloride. The tin dioxide-based nanomaterial includes palladium, antimony and tin dioxide. The mass ratio of the palladium element, the antimony element and the tin dioxide is (0.003-0.05): (0.0003-0.06): 1. For example, the mass ratio of the palladium element, the antimony element and the tin dioxide includes but is not limited to 0.003: 0.0003: 1, 0.01: 0.01: 1, 0.02: 0.02: 1, 0.03: 0.04: 1, 0.04: 0.05: 1, 0.041: 0.051: 1, 0.042: 0.052: 1, 0.045: 0.055: 1 or 0.05: 0.06: 1, or any two of the above ratios as endpoint values.

[0072] In one example, the process parameters of the heat treatment include: a treatment temperature of 400° C. to 600° C. For example, the temperature of the heat treatment includes but is not limited to 400° C., 420° C., 450° C., 470° C., 490° C., 500° C., 510° C., 530° C., 550° C., 570° C., 590° C. or 600° C., or a range formed by any two of the above point values ​​as endpoint values.

[0073] In one example, the process parameters of the heat treatment include: a treatment time of 1 h to 4 h. For example, the sintering treatment time includes but is not limited to 1 h, 2 h, 3 h or 4 h, or a range formed by any two of the above point values ​​as endpoint values.

[0074] In one example, the second solvent includes ethanol and water in a volume ratio of 1:(0.5-5). For example, the volume ratio of ethanol to water is 1:0.5, 1:0.8, 1:1, 1:1.5, 1:2, 1:2.5, 1:3, 1:3.5, 1:4, 1:4.5 or 1:5, or within a range formed by any two of the above point values ​​as endpoint values.

[0075] In one example, when the dispersant includes citrate, the steps of preparing the tin dioxide nanomaterial include:

[0076] S101, mixing a tin source and a citrate in a first solvent to prepare a mixed solution.

[0077] S201, adjusting the pH of the mixed solution to 3.8-13.5, performing a hydrothermal reaction, collecting the solid phase after solid-liquid separation, and preparing a microsphere precursor.

[0078] S301, sintering the microsphere precursor.

[0079] In another example, when the dispersant includes citrate, the steps of preparing the tin dioxide nanomaterial include:

[0080] S102, mixing a tin source and a citrate in a first solvent to prepare a mixed solution.

[0081] S202, adjusting the pH of the mixed solution to 3.8-13.5, performing a hydrothermal reaction, and collecting the solid phase after solid-liquid separation to prepare a microsphere precursor.

[0082] S302, sintering the microsphere precursor.

[0083] S402, mixing the sintered body obtained by sintering treatment and the doped metal source in a second solvent, drying, and then heat-treating to prepare the tin dioxide-based nanomaterial.

[0084] It is understandable that the doping metal source in step S402 includes one or more of antimony trichloride and palladium tetraaminonitrate. The types of raw materials and process parameters in the above steps are similar to those in the previous steps, so they will not be described here.

[0085] In one example, when the dispersant includes tetraamino palladium nitrate, the steps of preparing the tin dioxide nanomaterial include:

[0086] S103, mixing a tin source and tetraaminopalladium nitrate in a first solvent to prepare a mixed solution.

[0087] S203, adjusting the pH of the mixed solution to 3.8-13.5, performing a hydrothermal reaction, and collecting the solid phase after solid-liquid separation to prepare a microsphere precursor.

[0088] S303, sintering the microsphere precursor to prepare the tin dioxide nanomaterial.

[0089] In one example, when the dispersant includes tetraamino palladium nitrate, the steps of preparing the tin dioxide nanomaterial include:

[0090] S104, mixing a tin source and tetraaminopalladium nitrate in a first solvent to prepare a mixed solution.

[0091] S204, adjusting the pH of the mixed solution to 3.8-13.5, performing a hydrothermal reaction, and collecting the solid phase after solid-liquid separation to prepare a microsphere precursor.

[0092] S304, sintering the microsphere precursor.

[0093] S404, mixing the sintered body obtained by sintering treatment and the doped metal source in a second solvent, drying, and then performing heat treatment to prepare the tin dioxide-based nanomaterial.

[0094] It is understandable that the doping metal source in step S404 includes antimony trichloride. The types of raw materials and process parameters in the above steps are similar to those in the previous steps, so they will not be described in detail here.

[0095] In one example, the heat treatment is performed in an air atmosphere. In one example, in step S20, the reagent for adjusting the pH of the mixed solution to 3.8-13.5 is a pH adjuster, and the pH adjuster includes one or more of NaOH, KOH and ammonia water.

[0096] In one example, in step S20, the pH value of the mixed solution can be adjusted to any value between 3.8 and 13.5. For example, the pH value of the mixed solution includes but is not limited to 3.8, 4, 4.5, 5, 6, 7, 8, 9, 10, 11, 12, 12.2, 12.5, 12.8, 13, 13.2 or 13.5, or any two of the above points as endpoint values.

[0097] In one example, in step S20, the temperature of the hydrothermal reaction is 180° C. to 200° C. For example, the temperature of the hydrothermal reaction includes but is not limited to 180° C., 185° C., 190° C., 195° C. or 200° C., or a range formed by any two of the above point values ​​as endpoint values.

[0098] In one example, in step S20, the hydrothermal reaction time is 12 h to 24 h. For example, the hydrothermal reaction time includes but is not limited to 12 h, 13 h, 14 h, 15 h, 16 h, 17 h, 18 h, 19 h, 20 h, 21 h, 22 h, 23 h or 24 h, or a range formed by any two of the above point values ​​as endpoint values.

[0099] By limiting the temperature and time of the hydrothermal reaction, the reaction induction period of the tin dioxide precursor formation can be effectively shortened to improve production efficiency. At the same time, the temperature and time of the hydrothermal reaction are conducive to the formation of crystal nuclei and ensure the stability of the quality and performance of the product, which makes the chemical composition of the tin dioxide material uniform, so that when it is used in the sensor, the sensitivity, accuracy and stability of the response to the gas can be improved.

[0100] In one example, in step S30, the temperature of the sintering process is 400° C. to 600° C. For example, the temperature of the sintering process includes but is not limited to 400° C., 420° C., 450° C., 470° C., 490° C., 500° C., 510° C., 530° C., 550° C., 570° C., 590° C. or 600° C., or a range formed by any two of the above point values ​​as endpoint values.

[0101] In one example, in step S30, the sintering time is 1 hour to 4 hours. For example, the sintering time includes but is not limited to 1 hour, 2 hours, 3 hours or 4 hours, or a range formed by any two of the above points as endpoints.

[0102] Appropriate sintering temperature and time can make the tin dioxide nanomaterial more complete and stable. If the sintering temperature is slightly lower, the crystal growth will be incomplete, and there may be more defects and amorphous areas, affecting the performance of the material. If the sintering temperature is slightly higher, it may cause the crystal structure to be over-sintered, resulting in problems such as abnormal grain growth and grain boundary fusion. Therefore, limiting the sintering temperature and time can make the structure of the tin dioxide nanomaterial more stable, thereby improving the stability and repeatability of the gas sensing performance.

[0103] In a second aspect of the present application, a VOC gas sensor is provided, comprising a MEMS sheet and a gas-sensitive layer arranged on the surface of the MEMS sheet, wherein the gas-sensitive layer comprises a tin dioxide-based nanomaterial prepared by the preparation method described in any example of the first aspect of the present application.

[0104] In this application, "MEMS" is the abbreviation of Micro Electro Mechanical Systems, which means micro-electromechanical systems. MEMS has a tiny three-dimensional structure and is a general term for systems that process various input and output signals. The preparation steps of MEMS usually include film formation, photolithography, etching and other processes.

[0105] The third aspect of the present application provides a method for preparing the VOC gas sensor according to the second aspect of the present application, comprising the following steps:

[0106] P10. The tin dioxide-based nanomaterial prepared by the preparation method described in the first aspect of the present application is mixed with a third solvent to prepare a gas-sensitive layer slurry.

[0107] P20, coating the gas-sensitive layer slurry on the surface of the MEMS sheet, and after film formation, performing a solvent removal treatment to prepare the VOC gas sensor.

[0108] In one example, in step P10, the third solvent includes one or more of glycerol, ethylene glycol, 1,3-butanediol and deionized water.

[0109] In one example, in step P10, the mass concentration of the tin dioxide nanomaterial in the gas-sensitive layer slurry is 15% to 25%. For example, the mass concentration of the tin dioxide nanomaterial in the gas-sensitive layer slurry includes but is not limited to 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24% or 25%, or a range formed by any two of the above point values ​​as endpoint values.

[0110] In one example, in step P20, the method of applying the gas-sensitive layer slurry to the surface of the MEMS chip includes but is not limited to glue dispensing. Further, in the step of performing the glue dispensing process, the diameter of the glue dot is 0.0225 mm. 2 ~0.09 mm 2 .

[0111] In one example, in step P20, the film forming process parameters include: the film forming temperature is 120° C. to 150° C. Further, the film forming time is 50 min to 70 min.

[0112] In one example, in step P20, the process parameters of the desolventizing treatment include: a temperature of 280° C. to 320° C. Further, the time of the desolventizing treatment is 1.5 h to 3 h.

[0113] The following further specific examples are provided to explain the present application in detail. It should also be understood that the following examples are only used to further explain the present application and cannot be understood as limiting the scope of protection of the present application. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present application belong to the scope of protection of the present application. The specific process parameters of the following embodiments are also only examples within a suitable range, that is, those skilled in the art can make a selection within a suitable range through the description herein, and are not necessarily limited to the specific values ​​of the embodiments below.

[0114] Example 1

[0115] Embodiment 1 of the present application provides a MEMS gas sensor and a method for manufacturing the same, comprising the following steps:

[0116] Preparation of tin dioxide-based nanomaterials:

[0117] (1) 5 mmol (1.75 g) of SnCl4·5H2O (tin source) and 10 mmol (2.58 g) of sodium citrate were placed in a mixed solvent of anhydrous ethanol and deionized water (the volume ratio of anhydrous ethanol to deionized water was 1:3) and magnetically stirred for 15 min to prepare a mixed solution.

[0118] (2) Take 0.15 g of NaOH and add it to the mixed solution, adjust the pH to 3.9, continue magnetic stirring for 15 min, and then place it in a 50 mL polytetrafluoroethylene reactor and perform hydrothermal reaction at 180 °C for 12 h. After naturally cooling to room temperature, the sample is centrifuged. After solid-liquid separation, the solid phase is collected and the sample is centrifuged and washed three times with a mixed solvent of anhydrous ethanol and deionized water to prepare a microsphere precursor.

[0119] (3) The microsphere precursor was placed in a constant temperature drying oven (80°C) to be fully dried, and then placed in a muffle furnace for sintering with air as the background. The sintering temperature was 500°C for 2 hours. After naturally cooling to room temperature, the microsphere precursor was ground to prepare tin dioxide-based nanomaterials.

[0120] Preparation of MEMS gas sensor:

[0121] (1) Weigh 0.26 g of tin dioxide-based nanomaterial into a glass bottle, add 1.08 g of liquid phase (the liquid phase consists of propylene glycol, ethylene glycol, and 1,3-butanediol in a mass ratio of 50:47:3), stir and ultrasonicate to fully disperse the material and defoam it, and then prepare a gas-sensitive layer slurry.

[0122] (2) Apply the gas-sensitive layer slurry to the MEMS chip by dispensing (the size of the glue point is 0.0225 mm 2 ). After completion, leveling is performed and baking is performed at 150°C for 60 minutes to ensure film formation. Finally, sintering is performed at 300°C for 2 hours in a muffle furnace with air as the background to ensure that organic impurities are completely removed, and a MEMS gas sensor is obtained.

[0123] Example 2

[0124] Embodiment 2 of the present application provides a MEMS gas sensor and a method for manufacturing the same, comprising the following steps:

[0125] Preparation of tin dioxide-based nanomaterials:

[0126] (1) 2.5 mmol (0.88 g) of SnCl4·5H2O (tin source) and 5 mmol (1.29 g) of sodium citrate were placed in a mixed solvent of anhydrous ethanol and deionized water (the volume ratio of anhydrous ethanol to deionized water was 1:3) and magnetically stirred for 15 min to prepare a mixed solution.

[0127] (2) Take 0.075 g of NaOH and add it to the mixed solution, adjust the pH to 3.9, continue magnetic stirring for 15 min, and then place it in a 50 mL polytetrafluoroethylene reactor and perform hydrothermal reaction at 180 °C for 12 h. After naturally cooling to room temperature, the sample is centrifuged. After solid-liquid separation, the solid phase is collected and the sample is centrifuged and washed three times with a mixed solvent of anhydrous ethanol and deionized water to prepare a microsphere precursor.

[0128] (3) The microsphere precursor was placed in a constant temperature drying oven (80°C) to be fully dried, and then placed in a muffle furnace for sintering with air as the background. The sintering temperature was 500°C for 2 hours. After naturally cooling to room temperature, the microsphere precursor was ground to prepare tin dioxide-based nanomaterials.

[0129] Preparation of MEMS gas sensor:

[0130] (1) Weigh 0.26 g of tin dioxide-based nanomaterial into a glass bottle, add 1.08 g of liquid phase (the liquid phase consists of propylene glycol, ethylene glycol, and 1,3-butanediol in a mass ratio of 50:47:3), stir and ultrasonicate to fully disperse the material and defoam it, and then prepare a gas-sensitive layer slurry.

[0131] (2) Apply the gas-sensitive layer slurry to the MEMS chip by dispensing (the size of the glue point is 0.0225 mm 2 ). After completion, leveling is performed and baking is performed at 150°C for 60 minutes to ensure film formation. Finally, sintering is performed at 300°C for 2 hours in a muffle furnace with air as the background to ensure that organic impurities are completely removed, and a MEMS gas sensor is obtained.

[0132] Example 3

[0133] Embodiment 3 of the present application provides a MEMS gas sensor and a method for manufacturing the same, comprising the following steps:

[0134] Preparation of tin dioxide-based nanomaterials:

[0135] (1) 5 mmol (1.75 g) of SnCl4·5H2O (tin source) and 10 mmol (2.58 g) of sodium citrate were placed in a mixed solvent of anhydrous ethanol and deionized water (the volume ratio of anhydrous ethanol to deionized water was 1:3) and magnetically stirred for 15 min to prepare a mixed solution.

[0136] (2) Take 0.15 g of NaOH and add it to the mixed solution, adjust the pH to 3.9, continue magnetic stirring for 15 min, and then place it in a 50 mL polytetrafluoroethylene reactor and perform hydrothermal reaction at 180 ° C for 24 h. After naturally cooling to room temperature, the sample is centrifuged. After solid-liquid separation, the solid phase is collected and the sample is centrifuged and washed three times with a mixed solvent of anhydrous ethanol and deionized water to prepare a microsphere precursor.

[0137] (3) The microsphere precursor was placed in a constant temperature drying oven (80°C) to be fully dried, and then placed in a muffle furnace for sintering with air as the background. The sintering temperature was 500°C for 2 hours. After naturally cooling to room temperature, the microsphere precursor was ground to prepare tin dioxide-based nanomaterials.

[0138] Preparation of MEMS gas sensor:

[0139] (1) Weigh 0.26 g of tin dioxide-based nanomaterial into a glass bottle, add 1.08 g of liquid phase (the liquid phase consists of propylene glycol, ethylene glycol, and 1,3-butanediol in a mass ratio of 50:47:3), stir and ultrasonicate to fully disperse the material and defoam it, and then prepare a gas-sensitive layer slurry.

[0140] (2) Apply the gas-sensitive layer slurry to the MEMS chip by dispensing (the size of the glue point is 0.0225 mm 2 ). After completion, leveling is performed and baking is performed at 150°C for 60 minutes to ensure film formation. Finally, sintering is performed at 300°C for 2 hours in a muffle furnace with air as the background to ensure that organic impurities are completely removed, and a MEMS gas sensor is obtained.

[0141] Example 4

[0142] Embodiment 4 of the present application provides a MEMS gas sensor and a method for manufacturing the same, comprising the following steps:

[0143] Preparation of tin dioxide-based nanomaterials:

[0144] (1) 5 mmol (1.75 g) of SnCl4·5H2O (tin source) and 10 mmol (2.58 g) of sodium citrate were placed in a mixed solvent of anhydrous ethanol and deionized water (the volume ratio of anhydrous ethanol to deionized water was 1:3) and magnetically stirred for 15 min to prepare a mixed solution.

[0145] (2) Take 0.15 g of NaOH and add it to the mixed solution, adjust the pH to 3.9, continue magnetic stirring for 15 min, and then place it in a 50 mL polytetrafluoroethylene reactor and perform hydrothermal reaction at 200 °C for 12 h. After naturally cooling to room temperature, the sample is centrifuged. After solid-liquid separation, the solid phase is collected and the sample is centrifuged and washed three times with a mixed solvent of anhydrous ethanol and deionized water to prepare a microsphere precursor.

[0146] (3) The microsphere precursor was placed in a constant temperature drying oven (80°C) to be fully dried, and then placed in a muffle furnace for sintering with air as the background. The sintering temperature was 500°C for 2 hours. After naturally cooling to room temperature, the microsphere precursor was ground to prepare tin dioxide-based nanomaterials.

[0147] Preparation of MEMS gas sensor:

[0148] (1) Weigh 0.26 g of tin dioxide-based nanomaterial into a glass bottle, add 1.08 g of liquid phase (the liquid phase consists of propylene glycol, ethylene glycol, and 1,3-butanediol in a mass ratio of 50:47:3), stir and ultrasonicate to fully disperse the material and defoam it, and then prepare a gas-sensitive layer slurry.

[0149] (2) Apply the gas-sensitive layer slurry to the MEMS chip by dispensing (the size of the glue point is 0.0225 mm 2 ). After completion, leveling is performed and baking is performed at 150°C for 60 minutes to ensure film formation. Finally, sintering is performed at 300°C for 2 hours in a muffle furnace with air as the background to ensure that organic impurities are completely removed, and a MEMS gas sensor is obtained.

[0150] Example 5

[0151] Embodiment 5 of the present application provides a MEMS gas sensor and a method for manufacturing the same, comprising the following steps:

[0152] Preparation of tin dioxide-based nanomaterials:

[0153] (1) 5 mmol (1.75 g) of SnCl4·5H2O (tin source) and 10 mmol (2.58 g) of sodium citrate were placed in a mixed solvent of anhydrous ethanol and deionized water (the volume ratio of anhydrous ethanol to deionized water was 1:3) and magnetically stirred for 15 min to prepare a mixed solution.

[0154] (2) Take 0.175 g of NaOH and add it to the mixed solution, adjust the pH to 4.1, continue magnetic stirring for 15 min, and then place it in a 50 mL polytetrafluoroethylene reactor and perform hydrothermal reaction at 180 ° C for 12 h. After naturally cooling to room temperature, the sample is centrifuged. After solid-liquid separation, the solid phase is collected and the sample is centrifuged and washed three times with a mixed solvent of anhydrous ethanol and deionized water to prepare a microsphere precursor.

[0155] (3) The microsphere precursor was placed in a constant temperature drying oven (80°C) to be fully dried, and then placed in a muffle furnace for sintering with air as the background. The sintering temperature was 500°C for 2 hours. After naturally cooling to room temperature, the microsphere precursor was ground to prepare tin dioxide-based nanomaterials.

[0156] Preparation of MEMS gas sensor:

[0157] (1) Weigh 0.26 g of tin dioxide-based nanomaterial into a glass bottle, add 1.08 g of liquid phase (the liquid phase consists of propylene glycol, ethylene glycol, and 1,3-butanediol in a mass ratio of 50:47:3), stir and ultrasonicate to fully disperse the material and defoam it, and then prepare a gas-sensitive layer slurry.

[0158] (2) Apply the gas-sensitive layer slurry to the MEMS chip by dispensing (the size of the glue point is 0.0225 mm 2 ). After completion, leveling is performed and baking is performed at 150°C for 60 minutes to ensure film formation. Finally, sintering is performed at 300°C for 2 hours in a muffle furnace with air as the background to ensure that organic impurities are completely removed, and a MEMS gas sensor is obtained.

[0159] Example 6

[0160] Embodiment 6 of the present application provides a MEMS gas sensor and a method for manufacturing the same, comprising the following steps:

[0161] Preparation of tin dioxide-based nanomaterials:

[0162] (1) 3.33 mmol (1.17 g) of SnCl4·5H2O (tin source) and 0.06 g of an aqueous solution of tetraaminopalladium nitrate (the mass concentration of the aqueous solution of tetraaminopalladium nitrate is 10%) were placed in a mixed solvent of anhydrous ethanol and deionized water (the volume ratio of anhydrous ethanol to deionized water was 1:3), and a mixed solution was prepared after magnetic stirring for 15 min.

[0163] (2) NaOH was added to the mixed solution to adjust the pH to 13, and magnetic stirring was continued for 15 min. The mixture was then placed in a 50 mL polytetrafluoroethylene reactor and subjected to hydrothermal reaction at 180 °C for 12 h. After naturally cooling to room temperature, the sample was centrifuged. After solid-liquid separation, the solid phase was collected and washed three times by centrifugation with a mixed solvent of anhydrous ethanol and deionized water to prepare a microsphere precursor.

[0164] (3) The microsphere precursor is placed in a constant temperature drying oven (80°C) to be fully dried, and then placed in a muffle furnace for sintering with air as the background. The sintering temperature is 500°C for 2 hours. After naturally cooling to room temperature, the microsphere precursor is ground to prepare a tin dioxide-based nanomaterial. In the tin dioxide-based nanomaterial, the mass ratio of palladium element to tin dioxide is approximately 0.004:1.

[0165] Preparation of MEMS gas sensor:

[0166] (1) Weigh 0.26 g of tin dioxide-based nanomaterial into a glass bottle, add 1.08 g of liquid phase (the liquid phase consists of propylene glycol, ethylene glycol, and 1,3-butanediol in a mass ratio of 50:47:3), stir and ultrasonicate to fully disperse the material and defoam it, and then prepare a gas-sensitive layer slurry.

[0167] (2) Apply the gas-sensitive layer slurry to the MEMS chip by dispensing (the size of the glue point is 0.0225 mm 2 ). After completion, leveling is performed and baking is performed at 150°C for 60 minutes to ensure film formation. Finally, sintering is performed at 300°C for 2 hours in a muffle furnace with air as the background to ensure that organic impurities are completely removed, and a MEMS gas sensor is obtained.

[0168] Example 7

[0169] Embodiment 7 of the present application provides a MEMS gas sensor and a method for manufacturing the same, comprising the following steps:

[0170] Preparation of tin dioxide-based nanomaterials:

[0171] (1) 3.33 mmol (1.17 g) of SnCl4·5H2O (tin source) and 0.06 g of an aqueous solution of tetraaminopalladium nitrate (the mass concentration of the aqueous solution of tetraaminopalladium nitrate is 10%) were placed in a mixed solvent of anhydrous ethanol and deionized water (the volume ratio of anhydrous ethanol to deionized water was 1:3), and a mixed solution was prepared after magnetic stirring for 15 min.

[0172] (2) NaOH was added to the mixed solution to adjust the pH to 13, and magnetic stirring was continued for 15 min. The mixture was then placed in a 50 mL polytetrafluoroethylene reactor and subjected to hydrothermal reaction at 180 °C for 12 h. After naturally cooling to room temperature, the sample was centrifuged. After solid-liquid separation, the solid phase was collected and washed three times by centrifugation with a mixed solvent of anhydrous ethanol and deionized water to prepare a microsphere precursor.

[0173] (3) The microsphere precursor was placed in a constant temperature drying oven (80°C) to be fully dried, and then placed in a muffle furnace for sintering with air as the background. The sintering temperature was 500°C for 2 hours, and then naturally cooled to room temperature and ground.

[0174] (4) 0.5 g of the material obtained after grinding was placed in a container, and 4.17 g of antimony trichloride alcohol solution was added (wherein, the antimony trichloride alcohol solution was prepared by fully stirring and ultrasonically dispersing 0.1480 g of antimony trichloride and 12.2279 g of anhydrous ethanol), and then 20 ml of anhydrous ethanol was added. After fully magnetically stirring for 30 min, the material was placed in an oven at 80° C. for full drying, and then placed in a muffle furnace for heat treatment with air as the background at a temperature of 500° C. for 2 h. After naturally cooling to room temperature, the material was ground to obtain a tin dioxide-based nanomaterial; in the tin dioxide-based nanomaterial, the mass ratio of palladium element to tin dioxide was approximately 0.004:1; in the tin dioxide-based nanomaterial, the mass ratio of antimony element to tin dioxide was approximately 0.05:1.

[0175] Preparation of MEMS gas sensor:

[0176] (1) Weigh 0.26 g of tin dioxide-based nanomaterial into a glass bottle, add 1.08 g of liquid phase (the liquid phase consists of propylene glycol, ethylene glycol, and 1,3-butanediol in a mass ratio of 50:47:3), stir and ultrasonicate to fully disperse the material and defoam it, and then prepare a gas-sensitive layer slurry.

[0177] (2) Apply the gas-sensitive layer slurry to the MEMS chip by dispensing (the size of the glue point is 0.09 mm 2). After completion, leveling is performed and baking is performed at 150°C for 60 minutes to ensure film formation. Finally, sintering is performed at 300°C for 2 hours in a muffle furnace with air as the background to ensure that organic impurities are completely removed, and a MEMS gas sensor is obtained.

[0178] Example 8

[0179] Embodiment 8 of the present application provides a MEMS gas sensor and a method for manufacturing the same, comprising the following steps:

[0180] Preparation of tin dioxide-based nanomaterials:

[0181] (1) 3.33 mmol (1.17 g) of SnCl4·5H2O (tin source) and 0.13 g of an aqueous solution of tetraaminopalladium nitrate (the mass concentration of the aqueous solution of tetraaminopalladium nitrate is 10%) were placed in a mixed solvent of anhydrous ethanol and deionized water (the volume ratio of anhydrous ethanol to deionized water was 1:3), and a mixed solution was prepared after magnetic stirring for 15 min.

[0182] (2) NaOH was added to the mixed solution to adjust the pH to 13, and magnetic stirring was continued for 15 min. The mixture was then placed in a 50 mL polytetrafluoroethylene reactor and subjected to hydrothermal reaction at 180 °C for 12 h. After naturally cooling to room temperature, the sample was centrifuged. After solid-liquid separation, the solid phase was collected and washed three times by centrifugation with a mixed solvent of anhydrous ethanol and deionized water to prepare a microsphere precursor.

[0183] (3) The microsphere precursor is placed in a constant temperature drying oven (80°C) to be fully dried, and then placed in a muffle furnace for sintering with air as the background. The sintering temperature is 500°C for 2 hours. After naturally cooling to room temperature, the microsphere precursor is ground to prepare a tin dioxide-based nanomaterial. In the tin dioxide-based nanomaterial, the mass ratio of palladium element to tin dioxide is approximately 0.009:1.

[0184] Preparation of MEMS gas sensor:

[0185] (1) Weigh 0.26 g of tin dioxide-based nanomaterial into a glass bottle, add 1.08 g of liquid phase (the liquid phase consists of propylene glycol, ethylene glycol, and 1,3-butanediol in a mass ratio of 50:47:3), stir and ultrasonicate to fully disperse the material and defoam it, and then prepare a gas-sensitive layer slurry.

[0186] (2) Apply the gas-sensitive layer slurry to the MEMS chip by dispensing (the size of the glue point is 0.0225 mm 2 ). After completion, leveling is performed and baking is performed at 150°C for 60 minutes to ensure film formation. Finally, sintering is performed at 300°C for 2 hours in a muffle furnace with air as the background to ensure that organic impurities are completely removed, and a MEMS gas sensor is obtained.

[0187] Example 9

[0188] Embodiment 9 of the present application provides a MEMS gas sensor and a method for manufacturing the same, comprising the following steps:

[0189] Preparation of tin dioxide-based nanomaterials:

[0190] (1) 5 mmol (1.75 g) of SnCl4·5H2O (tin source) and 10 mmol (2.58 g) of sodium citrate were placed in a mixed solvent of anhydrous ethanol and deionized water (the volume ratio of anhydrous ethanol to deionized water was 1:3) and magnetically stirred for 15 min to prepare a mixed solution.

[0191] (2) Take 0.15 g of NaOH and add it to the mixed solution, adjust the pH to 3.9, continue magnetic stirring for 15 min, and then place it in a 50 mL polytetrafluoroethylene reactor and perform hydrothermal reaction at 180 ° C for 12 h. After naturally cooling to room temperature, the sample is centrifuged. After solid-liquid separation, the solid phase is collected and the sample is centrifuged and washed three times with a mixed solvent of anhydrous ethanol and deionized water to prepare a microsphere precursor.

[0192] (3) The microsphere precursor was placed in a constant temperature drying oven (80°C) to be fully dried, and then placed in a muffle furnace for sintering with air as the background. The sintering temperature was 500°C for 2 hours, and then naturally cooled to room temperature and ground.

[0193] (4) Weigh 0.5 g of the ground material and place it in a container, add 0.075 g of antimony trichloride alcohol solution (antimony trichloride alcohol solution configuration: 0.1480 g of antimony trichloride and 12.2279 g of anhydrous ethanol, fully stirred and ultrasonically dispersed), then add 20 ml of anhydrous ethanol, fully magnetically stir (30 min), place in an oven at 80°C to fully dry, then place in a muffle furnace for heat treatment with air as the background, the heat treatment temperature is 500°C, the time is 2 h, and after naturally cooling to room temperature, the material is ground to obtain a tin dioxide-based nanomaterial; in the tin dioxide-based nanomaterial, the mass ratio of antimony element to tin dioxide is approximately 0.0009:1.

[0194] Preparation of MEMS gas sensor:

[0195] (1) Weigh 0.26 g of tin dioxide-based nanomaterial into a glass bottle, add 1.08 g of liquid phase (the liquid phase consists of propylene glycol, ethylene glycol, and 1,3-butanediol in a mass ratio of 50:47:3), stir and ultrasonicate to fully disperse the material and defoam it, and then prepare a gas-sensitive layer slurry.

[0196] (2) Apply the gas-sensitive layer slurry to the MEMS chip by dispensing (the size of the glue point is 0.0225 mm 2). After completion, leveling is performed and baking is performed at 150°C for 60 minutes to ensure film formation. Finally, sintering is performed at 300°C for 2 hours in a muffle furnace with air as the background to ensure that organic impurities are completely removed, and a MEMS gas sensor is obtained.

[0197] Example 10

[0198] Embodiment 10 of the present application provides a MEMS gas sensor and a method for manufacturing the same, comprising the following steps:

[0199] Preparation of tin dioxide-based nanomaterials:

[0200] (1) 5 mmol (1.75 g) of SnCl4·5H2O (tin source) and 10 mmol (2.58 g) of sodium citrate were placed in a mixed solvent of anhydrous ethanol and deionized water (the volume ratio of anhydrous ethanol to deionized water was 1:3) and magnetically stirred for 15 min to prepare a mixed solution.

[0201] (2) Take 0.15 g of NaOH and add it to the mixed solution, adjust the pH to 3.9, continue magnetic stirring for 15 min, and then place it in a 50 mL polytetrafluoroethylene reactor and perform hydrothermal reaction at 180 ° C for 12 h. After naturally cooling to room temperature, the sample is centrifuged. After solid-liquid separation, the solid phase is collected and the sample is centrifuged and washed three times with a mixed solvent of anhydrous ethanol and deionized water to prepare a microsphere precursor.

[0202] (3) The microsphere precursor was placed in a constant temperature drying oven (80°C) to be fully dried, and then placed in a muffle furnace for sintering with air as the background. The sintering temperature was 500°C for 2 hours, and then naturally cooled to room temperature and ground.

[0203] (4) Weigh 0.5 g of the ground material and place it in a container, add 0.15 g of antimony trichloride alcohol solution (antimony trichloride alcohol solution configuration: 0.1480 g of antimony trichloride and 12.2279 g of anhydrous ethanol, fully stirred and ultrasonically dispersed), then add 20 ml of anhydrous ethanol, fully magnetically stir for 30 min, place in an oven at 80°C to fully dry, then place in a muffle furnace for heat treatment with air as the background, the heat treatment temperature is 500°C, the time is 2 h, and after naturally cooling to room temperature, the material is ground to obtain a tin dioxide-based nanomaterial; in the tin dioxide-based nanomaterial, the mass ratio of antimony element to tin dioxide is approximately 0.0019:1.

[0204] Preparation of MEMS gas sensor:

[0205] (1) Weigh 0.26 g of tin dioxide-based nanomaterial into a glass bottle, add 1.08 g of liquid phase (the liquid phase consists of propylene glycol, ethylene glycol, and 1,3-butanediol in a mass ratio of 50:47:3), stir and ultrasonicate to fully disperse the material and defoam it, and then prepare a gas-sensitive layer slurry.

[0206] (2) Apply the gas-sensitive layer slurry to the MEMS chip by dispensing (the size of the glue point is 0.0225 mm 2 ). After completion, leveling is performed and baking is performed at 150°C for 60 minutes to ensure film formation. Finally, sintering is performed at 300°C for 2 hours in a muffle furnace with air as the background to ensure that organic impurities are completely removed, and a MEMS gas sensor is obtained.

[0207] Embodiment 11

[0208] Embodiment 11 of the present application provides a MEMS gas sensor and a method for manufacturing the same, comprising the following steps:

[0209] Preparation of tin dioxide-based nanomaterials:

[0210] (1) 5 mmol (1.75 g) of SnCl4·5H2O (tin source) and 10 mmol (2.58 g) of sodium citrate were placed in a mixed solvent of anhydrous ethanol and deionized water (the volume ratio of anhydrous ethanol to deionized water was 1:3) and magnetically stirred for 15 min to prepare a mixed solution.

[0211] (2) Take 0.15 g of NaOH and add it to the mixed solution, adjust the pH to 3.9, continue magnetic stirring for 15 min, and then place it in a 50 mL polytetrafluoroethylene reactor and perform hydrothermal reaction at 180 ° C for 12 h. After naturally cooling to room temperature, the sample is centrifuged. After solid-liquid separation, the solid phase is collected and the sample is centrifuged and washed three times with a mixed solvent of anhydrous ethanol and deionized water to prepare a microsphere precursor.

[0212] (3) The microsphere precursor was placed in a constant temperature drying oven (80°C) to be fully dried, and then placed in a muffle furnace for sintering with air as the background. The sintering temperature was 500°C for 2 hours, and then naturally cooled to room temperature and ground.

[0213] (4) Weigh 0.5 g of the ground material and place it in a container, add 0.14 g of tetraaminopalladium nitrate aqueous solution (the mass concentration of tetraaminopalladium nitrate in the tetraaminopalladium nitrate aqueous solution is 10%), and then add 20 ml of anhydrous ethanol. After sufficient magnetic stirring (30 min), place it in an oven at 80°C to fully dry, and then place it in a muffle furnace for heat treatment with air as the background at a temperature of 500°C for 2 h. After naturally cooling to room temperature, the material is ground to obtain a tin dioxide-based nanomaterial; in the tin dioxide-based nanomaterial, the mass ratio of palladium element to tin dioxide is approximately 0.01:1.

[0214] Preparation of MEMS gas sensor:

[0215] (1) Weigh 0.26 g of tin dioxide-based nanomaterial into a glass bottle, add 1.08 g of liquid phase (the liquid phase consists of propylene glycol, ethylene glycol, and 1,3-butanediol in a mass ratio of 50:47:3), stir and ultrasonicate to fully disperse the material and defoam it, and then prepare a gas-sensitive layer slurry.

[0216] (2) Apply the gas-sensitive layer slurry to the MEMS chip by dispensing (the size of the glue point is 0.0225 mm 2 ). After completion, leveling is performed and baking is performed at 150°C for 60 minutes to ensure film formation. Finally, sintering is performed at 300°C for 2 hours in a muffle furnace with air as the background to ensure that organic impurities are completely removed, and a MEMS gas sensor is obtained.

[0217] Example 12

[0218] Embodiment 12 of the present application provides a MEMS gas sensor and a method for manufacturing the same, comprising the following steps:

[0219] Preparation of tin dioxide-based nanomaterials:

[0220] (1) 5 mmol (1.75 g) of SnCl4·5H2O (tin source) and 10 mmol (2.58 g) of sodium citrate were placed in a mixed solvent of anhydrous ethanol and deionized water (the volume ratio of anhydrous ethanol to deionized water was 1:3) and magnetically stirred for 15 min to prepare a mixed solution.

[0221] (2) Take 0.15 g of NaOH and add it to the mixed solution, adjust the pH to 3.9, continue magnetic stirring for 15 min, and then place it in a 50 mL polytetrafluoroethylene reactor and perform hydrothermal reaction at 180 ° C for 12 h. After naturally cooling to room temperature, the sample is centrifuged. After solid-liquid separation, the solid phase is collected and the sample is centrifuged and washed three times with a mixed solvent of anhydrous ethanol and deionized water to prepare a microsphere precursor.

[0222] (3) The microsphere precursor was placed in a constant temperature drying oven (80°C) to be fully dried, and then placed in a muffle furnace for sintering with air as the background. The sintering temperature was 500°C for 2 hours, and then naturally cooled to room temperature and ground.

[0223] (4) Weigh 0.5 g of the ground material and place it in a container, add 0.44 g of tetraamine palladium nitrate aqueous solution (the mass concentration of tetraamine palladium nitrate in the tetraamine palladium nitrate aqueous solution is 10%), and then add 20 ml of anhydrous ethanol. After sufficient magnetic stirring (30 min), place it in an oven at 80°C to fully dry, and then place it in a muffle furnace for heat treatment with air as the background at a temperature of 500°C for 2 h. After naturally cooling to room temperature, the material is ground to obtain a tin dioxide-based nanomaterial; in the tin dioxide-based nanomaterial, the mass ratio of palladium element to tin dioxide is approximately 0.03:1.

[0224] Preparation of MEMS gas sensor:

[0225] (1) Weigh 0.26 g of tin dioxide-based nanomaterial into a glass bottle, add 1.08 g of liquid phase (the liquid phase consists of propylene glycol, ethylene glycol, and 1,3-butanediol in a mass ratio of 50:47:3), stir and ultrasonicate to fully disperse the material and defoam it, and then prepare a gas-sensitive layer slurry.

[0226] (2) Apply the gas-sensitive layer slurry to the MEMS chip by dispensing (the size of the glue point is 0.0225 mm 2 ). After completion, leveling is performed and baking is performed at 150°C for 60 minutes to ensure film formation. Finally, sintering is performed at 300°C for 2 hours in a muffle furnace with air as the background to ensure that organic impurities are completely removed, and a MEMS gas sensor is obtained.

[0227] The tin dioxide-based nanomaterial prepared in Example 4 was subjected to SEM testing, and the corresponding SEM images are shown in FIG. Figure 1 shown.

[0228] The MEMS gas sensor prepared in the above embodiment was tested for gas sensing performance. The test method is as follows:

[0229] Work at constant power in an indoor environment at 10~40℃, RH:20~85%, and test the baseline resistance data Ra of the sensor in a closed constant gas test box according to the established time;

[0230] After the gas sensor is aged in a 30L test box for 24 hours, when the voltage curve is stable, use a micro-injector to extract 0.075μl of ethanol liquid and inject it into the gas box heater. After the ethanol evaporates and diffuses evenly, record the voltage value U of the voltage divider resistor. L , calculate the resistance according to the following formula:

[0231] Rg=(U*R L -U L *R L ) / U L Formula (1)

[0232] Rg: sensor sensitive loop resistance;

[0233] U: Total voltage of sensitive circuit, 5V;

[0234] RL: Standard voltage-dividing resistance value of sensitive circuit;

[0235] UL: Voltage across the voltage divider resistor in the sensitive circuit.

[0236] Then inject other volumes of ethanol respectively, test the voltage value UL of the voltage divider resistor of different concentrations of ethanol respectively, substitute it into formula (1) to calculate Rg, and calculate the sensitivity of different concentrations of ethanol according to the following formula:

[0237] Sensitivity = Ra / Rg-1.

[0238] The gas-sensing performance test results of the gas sensor of the embodiment to 0.5-100 ppm ethanol are shown in Table 1 below.

[0239] Table 1

[0240]

[0241] Example 1 is basically the same as Example 2. Compared with Example 1, the dosage of tin source, citrate, and pH regulator in Example 2 is slightly lower, resulting in the gas-sensing performance of the tin dioxide nanomaterial prepared therefrom being slightly worse than that in Example 1. Example 1 is basically the same as Example 3. Compared with Example 1, the hydrothermal reaction time in Example 3 is slightly longer, resulting in the gas-sensing performance of the tin dioxide nanomaterial prepared therefrom being slightly worse than that in Example 1. Example 1 is basically the same as Example 4. Compared with Example 1, the hydrothermal reaction temperature in Example 4 is slightly higher, resulting in the gas-sensing performance of the tin dioxide nanomaterial prepared therefrom being slightly worse than that in Example 1. Example 1 is basically the same as Example 5. Compared with Example 1, the dosage of pH regulator in Example 5 is slightly higher, and the gas-sensing performance of the tin dioxide nanomaterial prepared therefrom is better than that in Example 1.

[0242] In Example 6, the dispersant selected is a tetraamino palladium nitrate aqueous solution. Compared with Example 1, the amount of tin source used is lower, but the gas-sensing performance of the tin dioxide nanomaterial prepared in Example 6 is better than that in Example 1. This shows that the doping of palladium forms a heterojunction structure with tin dioxide, which can effectively improve the gas-sensing performance of the nanomaterial. Example 6 is basically the same as Example 7. Antimony is further doped in Example 7. It is found that the gas-sensing performance of the nanomaterial in Example 7 at a concentration of 1ppm is not much different from that of Example 6, but the gas-sensing performance at concentrations of 5ppm and 10ppm is greatly improved compared with Example 6. Example 6 is basically the same as Example 8. The amount of tetraamino palladium nitrate aqueous solution used in Example 8 is slightly higher than that in Example 6. It is found that the gas-sensing performance of the nanomaterial in Example 8 at concentrations of 1ppm and 5ppm is slightly worse than that of Example 6.

[0243] Example 9 is basically the same as Example 10, the main difference being that the amount of antimony doped in Example 9 and Example 10 is different, wherein Example 10 is doped with more antimony than Example 9, and its gas sensing performance is also better than Example 9. Example 11 is basically the same as Example 12, the main difference being that the amount of palladium doped in Example 11 and Example 12 is different, wherein Example 12 is doped with more palladium than Example 11, and its gas sensing performance is slightly worse than Example 11.

[0244] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0245] The above-described embodiments only express several implementation methods of the present application, which is convenient for understanding the technical solution of the present application in detail, but it cannot be understood as limiting the scope of protection of the invention patent. It should be pointed out that for ordinary technicians in this field, without departing from the concept of the present application, several modifications and improvements can be made, which all belong to the scope of protection of the present application. It should be understood that the technical solutions obtained by those skilled in the art through logical analysis, reasoning or limited experiments on the basis of the technical solutions provided in the present application are all within the scope of protection of the claims attached to the present application. Therefore, the scope of protection of the patent of this application shall be based on the content of the attached claims, and the description can be used to interpret the content of the claims.

Claims

1. A method for preparing a tin dioxide-based nanomaterial, characterized in that: The following steps are involved: Mixing a tin source and a dispersant in a first solvent to prepare a mixed solution; The pH of the mixed solution is adjusted to 3.8-13.5, a hydrothermal reaction is performed, and after solid-liquid separation, a solid phase is collected to prepare a microsphere precursor; The microsphere precursor is sintered to prepare the tin dioxide-based nanomaterial.

2. The method for preparing tin dioxide-based nanomaterials according to claim 1, characterized in that: The steps of preparing the mixed solution have one or more of the following characteristics: (1) The tin source includes one or more of SnCl4·5H2O, Na2SnO3 and SnCl2; (2) The first solvent includes an alcohol solvent and water in a volume ratio of 1: (0.5-5).

3. The method for preparing tin dioxide-based nanomaterials according to claim 1, characterized in that: The dispersant comprises a citrate; the citrate has one or more of the following characteristics: (1) The mass ratio of the tin source to the citrate is (0.8-1.8):(1.2-2.6); (2) The citrate includes one or more of sodium citrate, potassium citrate, ammonium citrate, zinc citrate and magnesium citrate.

4. The method for preparing tin dioxide-based nanomaterials according to claim 1, characterized in that: The dispersant includes tetraaminopalladium nitrate; The tin dioxide-based nanomaterial includes palladium element and tin dioxide, and the mass ratio of the palladium element to the tin dioxide is (0.003-0.05):

1.

5. The method for preparing the tin dioxide-based nanomaterial according to claim 3 or 4, characterized in that: After the step of sintering the microsphere precursor, the method further comprises: The sintered body obtained by sintering treatment and the doped metal source are mixed in a second solvent, and after removing the solvent, heat treatment is performed to prepare the tin dioxide-based nanomaterial.

6. The method for preparing tin dioxide-based nanomaterials according to claim 5, characterized in that: The preparation method has one or more of the following characteristics: (1) When the dispersant comprises citrate, the doping metal source comprises one or more of antimony trichloride and tetraaminopalladium nitrate; (2) When the dispersant includes tetraaminopalladium nitrate, the doping metal source includes antimony trichloride; (3) The process parameters of the heat treatment include: a treatment temperature of 400°C to 600°C and a treatment time of 1h to 4h.

7. The method for preparing the tin dioxide-based nanomaterial according to any one of claims 1 to 4, characterized in that: The step of preparing the microsphere precursor has one or more of the following characteristics: (1) The reagent for adjusting the pH of the mixed solution to 3.8-13.5 is a pH adjuster, and the pH adjuster includes one or more of NaOH, KOH and ammonia water; (2) The temperature of the hydrothermal reaction is 180°C to 200°C; (3) The hydrothermal reaction time is 12h~24h.

8. The method for preparing the tin dioxide-based nanomaterial according to any one of claims 1 to 4, characterized in that: The sintering process has one or more of the following characteristics: (1) The sintering temperature is 400°C to 600°C; (2) The sintering time is 1h~4h.

9. A VOC gas sensor, characterized in that: It comprises a MEMS sheet and a gas-sensitive layer arranged on the surface of the MEMS sheet, wherein the gas-sensitive layer comprises a tin dioxide-based nanomaterial prepared by the preparation method according to any one of claims 1 to 8.

10. A method for preparing a VOC gas sensor according to claim 9, characterized in that: The following steps are involved: Mixing the tin dioxide-based nanomaterial prepared by the preparation method according to any one of claims 1 to 8 with a third solvent to prepare a gas-sensitive layer slurry; The gas-sensitive layer slurry is coated on the surface of the MEMS sheet, and after film formation, a solvent removal treatment is performed to prepare the VOC gas sensor.